Aryltriolborates as Air- and Water-Stable Bases for Wittig Olefination - Huang, Wenhua; Zhao, Shuang-Hong; Xu, Ning (Synthesis, 2015)
Tetrabutylammonium aryltriolborates have been synthesized in 37–66% yield by a one-pot procedure from arylboronic acids, 1,1,1-tris(hydroxymethyl)ethane, and aqueous tetrabutylammonium hydroxide. The aryltriolborates can be used as bases in Wittig reactions of aromatic aldehydes with all three types of phosphorus ylides: stabilized and semistabilized ylides can be generated at room temperature, and nonstabilized ylides at 120 °C (bath temperature).
Keywords: tetrabutylammonium aryltriolborates; Wittig olefination; phosphorus ylides; organic bases; organoboron compounds